2015
DOI: 10.7150/ijms.10076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helixor A on Natural Killer Cell Activity in Endometriosis

Abstract: Background and Aim: NK cells are one of the major immune cells in endometriosis pathogenesis. While previous clinical studies have shown that helixor A to be an effective treatment for endometriosis, little is known about its mechanism of action, or its relationship with immune cells. The aim of this study is to investigate the effects of helixor A on Natural killer cell (NK cell) cytotoxicity in endometriosisMaterials and Methods: We performed an experimental study. Samples of peritoneal fluid were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…With regard to endometriosis, the cytotoxic function is reduced in peripheral and peritoneal NK cells. [53][54][55][56][57] Due to diminished cytotoxicity, retrograde endometrial cells are prone to survive in the peritoneal cavity, which results in the development of endometriosis. Factors controlling NK cell function have not been thoroughly investigated; however, several studies have shown that IL-6, 57 IL-15, 58 and transforming growth factor-β1 59 suppress NK cell cytotoxic activity.…”
Section: Reduced Nk Cell Cytotoxic Activity In Endometriosismentioning
confidence: 99%
See 3 more Smart Citations
“…With regard to endometriosis, the cytotoxic function is reduced in peripheral and peritoneal NK cells. [53][54][55][56][57] Due to diminished cytotoxicity, retrograde endometrial cells are prone to survive in the peritoneal cavity, which results in the development of endometriosis. Factors controlling NK cell function have not been thoroughly investigated; however, several studies have shown that IL-6, 57 IL-15, 58 and transforming growth factor-β1 59 suppress NK cell cytotoxic activity.…”
Section: Reduced Nk Cell Cytotoxic Activity In Endometriosismentioning
confidence: 99%
“…60 Further, an extract of the white mistletoe tree, Helixor A, also directly activates NK cell cytotoxicity. 56 By adapting a strategy for cancer immunotherapy, 61 Montenegro et al administered intraperitoneal injections of IL-2-activated NK cells and reduced lesion formation in a mouse endometriosis model. 62 In this manner, progress in developing cancer immunotherapies may provide new therapeutic options for endometriosis, and further development is expected.…”
Section: Activation Of Nk Cells: Potential For a New Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Markers of NK cell cytotoxicity include the natural receptors NKp46, NKp44, and NKG2D, CD16 (a cell surface marker), and CD107a [ 42 ] and CD69 (markers of activation). The levels of all of these markers are significantly reduced in the peritoneal NK cells of endometriosis patients.…”
Section: An Altered Nk Cell Phenotype In the Peritoneal Cavitymentioning
confidence: 99%